Long-term dynamics of the composition, structure and state of tree stands of northern taiga pine forests in the European North-East of Russia - I. N. Kutyavin; A. V. Manov; A. F. Osipov; K. S. Bobkova (Сибирский лесной журнал, 2023)
The results of long-term observations in pine tree stands of bilberry and sphagnum forest types are presented. The studies were carried out in the northern subzone taiga conditions of the European North-East of Russia. The method of observation on permanent sample plots was used (the period from 1967 to 2016). Pine tree stands develop on old logging areas (about 70 years ago) and after fire sites. Based on the results of observations carried out significant changes in the morphometric parameters of pine (Pinus L.) trees and stands were established. In pine forests formed on logging areas, high values of the coefficients of variation of trees in terms of density and stock of stem wood (from 30 to 130 %) were revealed. Such high variation coefficients indicate their active formation. In post-pyrogenic naturally developing pine forests, the coefficients of variation of indicators vary from small (10 %) to high (40 %) values. In bilberry pine forests formed after logging, there is a tendency to reduce the density of trees, mainly caused by the loss of birch (Betula L.) and aspen (Populus tremula L.). Whereas, in sphagnum types pine forests, an active replenishment of forest stands with small pine trees from undergrowth was noted. It has been established that with an increase in the proportion of young generation of pine in the composition of forest stands, both a decrease in the average and current growth in stock, as well as a weakening of the vital state and an increase in damage to pine trees occur. During the observation period, the vital state of the most pine forest stands is characterized as «healthy status». In sphagnum types pine forests, the vital state of forest stands is somewhat weaker than in bilberry pine forests. This is due to the unfavorable conditions of their growth on waterlogged soils.